2022
DOI: 10.1515/biol-2022-0520
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drought tolerance indices in faba bean genotypes under different irrigation regimes

Abstract: Drought stress has devastating impacts on faba bean production, particularly with the current abrupt climate changes in arid environments. Hence, it is essential to identify drought-tolerant genotypes. The present study aimed at assessing six faba bean genotypes under three irrigation levels during two winter successive growing seasons (2018/2019 and 2019/2020). The applied irrigation levels were well-watered (every 4 days (D1), moderate drought every 8 days (D2), and severe drought 12 days (D3)) regimes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Several previous studies reported decreased chlorophyll content for plants exposed to extremely dry conditions, depending on the period of drought [59]. Leaf chlorophyll content is shown to increase during an early stage of water stress and decrease gradually with increasing periods of drought [60]. The results of this study showed that leaf chlorophyll content was greatly reduced in drought-stressed tomato plants, indicating that water stress negatively affected chlorophyll synthesis, as illustrated in many previous studies.…”
Section: Spad Chlorophyll Contentsupporting
confidence: 80%
“…Several previous studies reported decreased chlorophyll content for plants exposed to extremely dry conditions, depending on the period of drought [59]. Leaf chlorophyll content is shown to increase during an early stage of water stress and decrease gradually with increasing periods of drought [60]. The results of this study showed that leaf chlorophyll content was greatly reduced in drought-stressed tomato plants, indicating that water stress negatively affected chlorophyll synthesis, as illustrated in many previous studies.…”
Section: Spad Chlorophyll Contentsupporting
confidence: 80%
“…In this concern, many researchers found that exposing faba bean plants to inadequate moisture caused a reduction in RWC % and total chl. (Abdel Samie et al, 2021;Abdelhaleim et al, 2022) and TWC% (El-Gabry & Morsi, 2019).…”
Section: Physiological Attributesmentioning
confidence: 99%
“…increasing irrigation intervals (El -Metwally et al, 2007), skipping irrigation number (Ibrahim, 2011) and decreasing either water applied (Fouda et al, 2022) or number of irrigations (Eid et al, 2008). Other investigators found that exposing faba bean plants to any water drought stress caused a significant damaging for plant growth (Oukaltouma et al, 2021;Abdelhaleim et al, 2022), seed yield/ plant and its components (El-Emshaty et al, 2021;Yousry et al, 2021) and seed yield/ fed (Abdel-Ghany et al, 2016;EL-Mansoury & Saleh, 2017) but led to an increase in protein % (Mekkei, 2014;Megawer et al, 2017) and water use efficiency (Abdel Samie et al, 2021;Noreldin & Abd-Alla, 2022). Moreover, Fakkar et al (2016), Tawfik et al (2018) and El-Gabry & Morsi (2019) found that the faba bean cultivars differed in their behaviour and seed and water productivity under various drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean, Vicia faba L. (Family: Fabaceae) is one of the oldest economic legume crops globally (Elsebaie et al 2022) which is believed to be originated in the Near East (Merga et al 2019). Worldwide, the most producing countries of this crop are China, Ethiopia, France, Egypt, and Australia (Abdelhaleim et al 2022). In Egypt, V. faba is considered the most popular nutritive crop and stable food in the Egyptian diet (El-Metwally et al 2017).…”
Section: Introductionmentioning
confidence: 99%